– The Grammar Expansion in the Saudi Press – Okaz Newspaper as a Model - Al- Adbaay, Abdul Ghani Shawqi; Baitish, Yahya (Arab Journal for Sciences and Research Publishing, 2018)
This study examines the problem of the expansion of the media language or the use of grammatical structures, including the expansion of grammatical order and the creation of new grammatical functions for some words, as well as the deletions in the parts of the sentence and the separation between the two integrals, It also presents some of the structures that are contrary to grammatical rules in the expression.
Keywords: Grammatical expansion; Grammatical order; Grammatical function; Separation of related elements; Parsing